Persepsi Masyarakat Terhadap Lembaga Keuangan Mikro Syariah Khususnya Bank Wakaf Mikro Di Kota Medan - Nanda Ardiansyah; Eri Yanti Nasution; Prawidya Hariani RS (Inovatif: Jurnal Ekonomi, Manajemen, Akuntansi, Bisnis Digital dan Kewirausahaan, 2023)
This study aimed to determine the factors that influence public perception of Islamic microfinance institutions, especially micro waqf banks in Medan. Sampling was carried out using the non-probability sampling method of 100 people from the community around the Mawaridussalam Islamic Boarding School, Tumpatan Nibung Village, Batang Kuis District, Deli Serdang Regency, North Sumatra. Test data analysis using factor analysis to see the most dominant factors that form variables. The results showed that the most influential factors were attention and personality towards the perceptions of the people around the Mawaridussalam Islamic Boarding School area.